Student’s Self-Efficacy In Integrating Islamic And Scientific Knowledge: An Analytical Study - Nur Fazwanis Othman; Syed Najihuddin Syed Hassan; Robiatul Adawiyah Mohd @ Amat (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI005 52-59